Wear of Medium Carbon Steel under Friction Loading with Various Contact Surface Temperature - Widiyarta, I Made; Parwata, I Made; Lokantara, I Putu; Dwipayana, Dwipayana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
The work presented in this paper is to investigate the wear rate and wear mechanism of medium carbon steel with carbon contents of about 0,5 wt.% under the friction load with various contact surface temperatures. The wear test was performed by using the linear reciprocating ball-on-flat wear test machine. To develop the elevated temperature on the surface of the wear test specimen, the heater assembled into the wear test machine. The surface temperature of the wear specimen was set in the range of 30 ºC up to 250 ºC. The test was taken under 5000 cycles of friction loading with a maximum of the normal load of 25N. The experiment results show that the change in the contact surface temperature in the range of 30 ºC up to 250 ºC causes the wear rate to increase slightly. This is because the elevated temperature at the surface was not high enough to cause the hardness of the material to decrease significantly. The worn surface looks very thin scratches and slightly deformed layers, and the wear mechanism had identified as oxide wear.